Optimization of UWB Array Antenna for Bio-Medical Applications Using Cuckoo Search Algorithm - Rajkamal, K; Immadi, Govardhani. (International Journal of Engineering and Technology, 2018)
A four-element microstrip antenna array is designed in which the array is made using Wilkinson power dividers and four identical patch antenna elements. The elements of the designed array are perfectly developed to get a constant gain and have a compact size against the frequency. Using the microstrip technology equipment a prototype can be build to enhance the directivity, return loss and also its return loss and radiation pattern. The antenna array that is put forth here comprises of two major parts which are the array of the antennas and also its power network. In many of the important applications like biomedical, communication and also radio frequency applications the power divider plays a crucial role. Power dividers also function as the power networks of the array of antennas. An equal division power divider is generally required to synthesize the radiation pattern. Here a very new design for a power splitter having the same square sector of four ports and also its application is also presented. Techniques like insertion and also insertion fitting techniques were employed to adjust or alter the phase and amplitude of the signals that are exiting each branch of the power divider. The impedances of the branches are adjusted according to the required power ratio by using the pairing techniques. Electromagnetic Solvers which are based on MOM used in the design process. The parameters using which the power divider is made up of is the dielectric constant Er=4.3,loss tangent of 0.02 and height of 1.6mm.Along with the design of the ultra wide band antenna is also designed. Finally some of the optimization techniques such as the fly flight algorithm, cuckoo search algorithm, spring cuckoo algorithm for reducing mutual coupling and improving antenna parameters such as return loss, gain pattern, directivity and radiation. The experimental measurements are made using the network vector analyzer. A good agreement was found between the measurements and the results of the simulation.Â Â